Airborne particulate matter increases MUC5AC expression by downregulating Claudin-1 expression in human airway cells - Kim, Sang-Su; Kim, Cheol Hong; Kim, Ji Wook; Kung, Hsi Chiang; Park, Tae Woo; Shin, Yu Som; Kim, Ju Deok; Ryu, Siejeong; Kim, Wang-Joon; Choi, Yung Hyun; Song, Kyoung Seob (BMB reports, 2017)
CLB2.0, a constituent of PM, induces secretion of multiple cytokines and chemokines that regulate airway inflammation. Specifically, IL-6 upregulates CLB2.0-induced MUC5AC and MUC1 expression. Interestingly, of the tight junction proteins examined, claudin-1 expression was inhibited by CLB2.0. While the overexpression of claudin-1 decreased CLB2.0-induced MUC5AC expression, it increased the expression of the anti-inflammatory mucin, MUC1. CLB2.0-induced IL-6 secretion was mediated by ROS. The ROS scavenger N-acetylcysteine inhibited CLB2.0-induced IL-6 secretion, thereby decreasing the CLB2.0-induced MUC5AC expression, whereas CLB2.0-induced MUC1 expression increased. CLB2.0 activated the ERK1/2 MAPK via a ROS-dependent pathway. ERK1/2 downregulated the claudin-1 and MUC1 expressions, whereas it dramatically increased CLB2.0-induced MUC5AC expression. These findings suggest that CLB2.0-induced ERK1/2 activation acts as a switch for regulating inflammatory conditions though a ROS-dependent pathway. Our data also suggest that secreted IL-6 regulates CLB2.0-induced MUC5AC and MUC1 expression via ROS-mediated downregulation of claudin-1 expression to maintain mucus homeostasis in the airway. [BMB Reports 2017; 50(10): 516-521].